Fatigue growth analyses of a part-through crack in a solid bar under combined cyclic tension-torsion loading / Devi Chandra - Devi, Chandra (2016)
This thesis presents evaluations of the stress intensity factors (SIFs) and the fatigue crack growths of a surface/corner crack in solid bar under combined cyclic tension-torsion loading. A surface crack in solid cylinder and a corner crack in square prismatic bar are considered. The numerical modelling was carried out using a Dual Boundary Element Method (DBEM) based software and an axial-torsion fatigue testing machine was utilized to perform the experimental works. In doing the numerical works, the J-integral technique was chosen to evaluate the stress intensity factors and the NASGRO crack growth rate equation was used to simulate the fatigue crack growths. As preliminary numerical works, fatigue crack growths of a surface crack in a notched cylinder under cyclic tension were evaluated. Crack shape evolutions for different crack aspect ratios and the corresponding stress intensity factors were correlated to study the behaviour of the crack growths. The cylinder that contains a defect which has a smaller crack aspect ratio in a notched cylinder shall be given more careful attentions. Next, the numerical works were further carried out to evaluate the stress intensity factors and fatigue crack growths of a corner crack in a square prismatic bar under combined cyclic torsion-tension loads. In this particular case, the cylinder part was needed to model the torsional loading to be transferred to the square bar. The SIFs at the initial condition and the fatigue crack growths for different loading ratios of tension stress to torsional stress are presented. For a given tension loading, the larger Mode III SIFs and the shorter fatigue life were found at the model with the crack aspect ratio a/c ≠ 1 and having a larger torsional loading. With a consideration of a practical interest, surface crack growths in a solid cylinder under combined cyclic tension-torsion loading were particularly evaluated through experimentation and numerical modeling. The aluminium alloy 6061-T6 was used for this purpose. A guideline for introducing a semi-elliptical surface crack in a solid cylinder using the die-sinking EDM machine is presented in detail in this thesis. iv The numerical simulations and experimental works showed similar crack growth paths. The fatigue lives obtained from the experimentation and numerical simulations were shown to be in good agreements. At the first increment, the torsion loading gave a more dominant effect on the crack extension angle at the crossed surface point than that due to the crack aspect ratio. Meanwhile, the effect of the crack aspect ratio on the crack extension angle was observed to be more dominant at the crack depth point. The combinations of flat and shear lips fracture surfaces, and fluctuating crack growth direction and Keff values at the crossed surface points confirmed the inclined and twisted crack front during stable crack growth. The crack growth direction at the crossed surface points fluctuated significantly during stable crack growth.